Hybrid and Advanced Technologies : Proceedings of the International Conference on Hybrid and Advanced Technologies (ICHAT 2024), April 26-28, 2024, Ongole, Andhra Pradesh, India (Volume 2) - S. Prasad Jones Christydass; Nurhayati Nurhayati; S. Kannadhasan (CRC Press, 2025)
The proceedings of the International Conference on Hybrid and Advanced Technologies (ICHAT 2024) present a rich repository of cutting-edge research on the various applications of machine learning, deep learning, and AI in cybersecurity, healthcare, agriculture and communication systems.It highlights the revolutionary potential of data science in transforming traditional practices, improving efficiency and accuracy across diverse domains and addressing complex real-world challenges. These proceedings contains innovative neural-network models for agriculture that can predict tractor fuel consumption and optimize smart irrigation, besides suggesting greenhouse automation for enhanced agricultural productivity. It also provides a roadmap for IoT-based monitoring systems for asthma patients and machine learning approaches for early detection of diabetes, cancer and aquatic plant ailments. Through an array of practical examples and comparative studies, the book further highlights advancements in machine learning for enhancing palm vein authentication, combating fake news, keeping data safe and improving customer segmentation in e-commerce. The findings would be instrumental in combating critical global issues and foster a deeper understanding of the role of AI in image processing, cybersecurity, medical diagnostics, and intelligent systems in the future.This will be a highly interesting guide to researchers, data scientists, and practicing professionals in the fields of artificial intelligence, machine learning, and cybersecurity. It will also be of interest to healthcare professionals, agricultural scientists, and technology enthusiasts in fostering global collaborations, exploring future challenges and opportunities and introducing state-of-the-art technologies to streamline processes.